Gametogenic cycle of the rock boring urchin Echinometra lucunter (Echinodermata: Echinoidea) in northeastern Venezuela. - Reyes-Luján, Jeny (2015)
Several species of sea urchins are a potential resource for the production of gonads for consumption in Venezuela. We studied the gametogenic cycle and the gonadosomatic index (GSI) of the rock boring urchin Echinometra lucunter between June 2010 and November 2011 in northeastern Venezuela (Isla Lobos, Península de Araya and Turpialito, Gulf of Cariaco). The gonads are composed of long ramified acini, covered by connective tissue, followed by a thin layer of cells that differentiate into nutritive phagocytes and gametes, which change in their proportion and size with the maturity stage. Generally, several maturity stages were observed in both locations, showing simultaneous spawning. At Isla de Lobos the individuals in reserve stage predominated with a short period of sexual maturity, while mature and spawned individuals predominated in Turpialito. The GSI suggests that the greatest spawning activity is associated to the rainy season; showing a conservative reproductive activity, accruing energetic reserves during the period of higher primary productivity associated to coastal upwelling, when the energy of nutritive phagocytes is transferred to gametes, for gamete development and spawning. The biological and reproductive characteristics of individuals at Turpialito showed higher GSI having more gonadal tissue for commercial consumption.